Gut microbiome and reproductive endocrine diseases: a Mendelian randomization study - Liang, Ye; Zeng, Weihong; Hou, Tao; Yang, Haikun; Wu, Boming; Pan, Ru; Huang, Lishan (Frontiers in Endocrinology, 2023)
Background Observation studies have confirmed the association between gut microbiome and reproductive endocrine diseases (REDs), namely polycystic ovary syndrome (PCOS), endometriosis, and female infertility. However, their association has never been confirmed by a two-sample Mendelian randomization (MR) analysis. Methods: We conducted a two-sample MR analysis to evaluate therelationship between gut microbiome and three above REDs. In order to get more comprehensive results, two different thresholds were adopted to select instrumental variables (IVs): one was locus-wide significance threshold (P <1.0×10–5) and the other was genome-wide significance level (P< 5×10-8). Summary-level statistics for gut microbiome and REDs were collected from public databases. Inverse variance weighted (IVW) is the main method to estimate causality, and sensitivity analyses were conducted to validate MR results. Results: At the locus-wide significance level, we identified that the genus Streptococcus (OR=1.52, 95%CI: 1.13-2.06, P=0.006) and RuminococcaceaeUCG005 (OR=1.39, 95%CI: 1.04-1.86, P=0.028) were associated with a high risk of PCOS, while Sellimonas(OR= 0.69, 95%CI: 0.58-0.83, P=0.0001) and RuminococcaceaeUCG011(OR=0.76, 95%CI: 0.60-0.95, P=0.017)were linked to a low PCOS risk. Genus Coprococcus2(OR=1.20, 95%CI: 1.01-1.43, P=0.039) was correlated with an increased risk of female infertility, while Ruminococcustorques (OR=0.69, 95%CI: 0.54-0.88, P=0.002) were negatively associated with the risk of female infertility. Genus Olsenella (OR= 1.11, 95%CI: 1.01-1.22, P=0.036), Anaerotruncus (OR= 1.25, 95%CI: 1.03-1.53, P=0.025), and Oscillospira (OR= 1.21, 95%CI: 1.01-1.46, P=0.035) were linked to a high risk of endometriosis. However, the results showed that gut microbiome had not a causal link with REDs risk based on the genome-wide significance level. Sensitivity analyses further confirmed the robustness of MR results. Conclusion: Our study provides evidence that gut microbiome is closely related with REDs. Subsequent studies should be conducted to promote microbiome-orientated therapeutic strategies for managing REDs.